The effect of unstable job on employee's turnover intention: The importance of coaching leadership - Jeyong Jung; Byung-Jik Kim; Byung-Jik Kim; Min-Jik Kim (Frontiers in Public Health, 2023)
Swift social and economic environmental changes such as COVID-19 pandemic have led to increased job insecurity. The current study examines the intermediating mechanism (i.e., mediator) and its contingent factor (i.e., moderator) in the association between job insecurity and employee's turnover intention, especially from the perspective of positive psychology. By establishing a moderated mediation model, this research hypothesizes that the degree of employee meaningfulness in work may mediate the relationship between job insecurity and turnover intention. In addition, coaching leadership may play a buffering role to positively moderate the harmful impact of job insecurity on meaningfulness of work. With three-wave time-lagged data that was collected from 372 employees in South Korean organizations, the current study not only demonstrated that meaningfulness of work mediates the job insecurity–turnover intention relationship, but also that coaching leadership functions as a buffering factor in reducing the harmful influence of job insecurity on meaningfulness of work. The results of this research suggest that the level of meaningfulness of work (as a mediator) as well as coaching leadership (as a moderator) are the underlying processes and the contingent factor in the job insecurity–turnover intention link.